2018
DOI: 10.1007/s00213-018-5057-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reacquisition of contextual fear following extinction in mice: effects of amount of extinction, acute ethanol withdrawal, and ethanol intoxication

Abstract: Rationale: Many studies have found that ethanol intoxication and withdrawal impairs initial acquisition or extinction of learned behaviors. Rapid reconditioning following extinction is a form of post-extinction re-emergence of conditioned behavior that has not been studied for its interaction with ethanol intoxication or withdrawal. Objectives: The goals of this paper were to define the parameters that allow rapid post-extinction reacquisition of fear in mice and investigate the effect of acute ethanol withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…This is in contrast to our previous work with mice, which found that extensive extinction eliminated rapid reconditioning (Williams and Lattal 2019). The slow rate of reacquisition that sometimes occurs could be due to a number of factors, including performance variables and differences in exposure to the context causing latent inhibition (Bouton and Swartzentruber 1989;Brooks et al 2003;Williams and Lattal 2019). We found that extensive context preexposure did appear to weaken initial conditioning, but this was not specific to the context of preexposure (Experiment 3).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This is in contrast to our previous work with mice, which found that extensive extinction eliminated rapid reconditioning (Williams and Lattal 2019). The slow rate of reacquisition that sometimes occurs could be due to a number of factors, including performance variables and differences in exposure to the context causing latent inhibition (Bouton and Swartzentruber 1989;Brooks et al 2003;Williams and Lattal 2019). We found that extensive context preexposure did appear to weaken initial conditioning, but this was not specific to the context of preexposure (Experiment 3).…”
Section: Discussionmentioning
confidence: 61%
“…This effect was not always robust (e.g., Group REC 3 EXT in Experiment 2), but there was no evidence that postextinction reconditioning was impaired relative to initial conditioning. There are many demonstrations that massive extinction may slow reacquisition (Bouton 1986;Leung et al 2007) and we have previously found that massive extinction impairs rapid reacquisition of contextual fear in mice (Williams and Lattal 2019). It is notable that in Experiments 1-3 freezing extinguished quickly and showed little spontaneous recovery across extinction sessions.…”
Section: Experiments 4: Reconditioning After Short or Long Extinction mentioning
confidence: 70%
See 2 more Smart Citations
“…Considering the comorbidity between anxiety disorders and alcohol addiction, the interaction of pharmacological processes associated with addiction—such as alcohol withdrawal—and prolonged exposure therapy is potentially of great clinical impact. This relationship is addressed by Williams and Lattal (2019), with their data highlighting the complex relationship between fear learning and drug withdrawal. However, there are commonalities between fear and drug memory extinction, particularly with respect to the impact of individual differences on long-term behavioural outcomes.…”
Section: The Psychopharmacology Of Reward and Drug Extinctionmentioning
confidence: 99%